Assessment of Root Anatomy and Variations of Third Mandibular Molars in the Population of Peshawar using Cone Beam Computed Tomography - Asma Amir, Imran Qureshi, Ambereen Humayun, Farooq Khan, Imran Khattak, Yusra Jamil Khattak, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Third molars have root canal structure that is frequently incredibly complicated and highly varied. Greater heterogeneity in root patterns and canal shape has been linked to mandibular third molars. Aim: To assess the root and canal anatomy of mandibular third molar in the people of Peshawar using cone beam computed tomography. Study Design: Retrospective study. Place and Duration of Study: Khyber College of Dentistry and Rehman College of Dentistry, from 1st December 2020 to 31st January 2022. Methodology: One hundred and ninety five CBCT scans of third mandibular molars were examined and the data in regards to their root number, canal number, Vertucci’s classification, gender and age relation of morphology in mandibular third molars was statistically assessed. Results: Greater number of 3rdmandibular molars had two roots (89.7%) and two canals (67.7%). Most mesial roots had Vertucci Type I (61%), distal root had type I canals as well (92.8%) Conclusion: The current study concluded that mandibular third molars showed great variation in Root canal configuration. Majority had two roots and two canals per root. Keywords: Canal configuration, Vertucci’s classification, Mandibular third molars, Cone beam computed tomography (CBCT)